Iowa Birdline update, January 15, 1994 - Scheib, Jameset al; Iowa Ornithologists' Unionet al (1994)
Notes for the Iowa Birdline update for January 15, 1994. Highlights include a Varied Thrush, Common Redpolls and a Snowy Owl. Epson - sheet feed/flatbed